Scheduling of batch process plant / Aladin Awang Hamat - Hamat, Aladin Awang (1999)
Batch processing is widely used in many industries. This is because, nowadays industries produce higher quality products in small quantities, thus to justify the economie cost of continuous production equipment. For that reason, this research is done based on the development of scheduling, involving algorithm and hardware. The control algorithm approach for batch process plant is used as Dijekstra's algorithm. For analysis purposes, the computer can accept this environment. The application of Visual basic 6.0 software is introduced to run the system. The graphical presentation and simulations will give some ideas to user how the system works. Three LEDs (light emitting diode) were chosen as the right hardware to represent the actual events of process in real life. The LED's indicators can be represented as a plant, de motor or el se, which is control by the algorithm.